TEACHER-STUDENTS BONDING IN MATHEMATICS LEARNING: AN EXPLORATION OF PAST, PRESENT AND FUTURE - Dahal, Niroj (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2020)
This piece of writing describes my lived experience as journeying of my educational practices as teacher(s), teacher educator and novice researcher high lightings on the bonding between teacher(s) as facilitator(s) in past, present, and future aligned with possible transformation from conventional to modern methods in teaching mathematics for 21st-century learners. As per the experiences as a teacher of mathematics in various institutions in distinct time, the ambition of this piece of writing is basically intended to study and investigate profound settled conventional practices in past, present and future-looking forward to the expected transformation towards modern/constructivist way of teaching and learning in relation to bonding between teacher and students for quality in facilitating the 21st-century learners in Nepal. Endorsing interpretive, critical, and postmodern research paradigms to grasp multi- paradigmatic research design (Taylor, Taylor & Luitel, 2012 as cited in Dahal, 2013); I used auto-ethnography as a noble and emerging research methodology for this inquiry. In addition, auto-ethnographic research has assisted me to study the pedagogical and cultural learning from various outlooks in relation to teachers, educational researchers, and educator-educators, in acting so whatever offers the room for interpretation, transformation and envisioning. I concluded by means of the thoughts that students’ energetic involvement in learning and transformative pedagogy assists the practice(s) to be more significant and learner-centered which in move results in better bonding in understanding the learners. My vision to develop a better bonding is highlighted a bit uniquely in this piece of writing with the possible implication(s) for mathematics facilitator(s).